Tragedy, Logic, and Action in Hegel’s Outlines of the Philosophy of Right (Encuentros, 2024)
The text examines the interconnection between tragedy, logic, and action in Hegel's works, notably in "Outlines of the Philosophy of Right." Hegel correlates tragedy with negativity and reconciliation, influenced by ancient tragedy and Christian consciousness. Tragedy serves as a means for self-knowledge, where negativity and death are pivotal in unveiling the spirit’s truth. Hegel’s philosophy is enriched by the works of Aeschylus and Sophocles, depicting the ethical crisis in Athens and the ensuing reconciliation of opposing ethical forces. Hegel identifies tragic elements in Christianity, a religion that perceives death and contradiction not as endpoints but transitional phases in reality. Christian religious consciousness, marked by finitude and sin, seeks reconciliation between the mutable and immutable. Hegel’s practical philosophy is grounded in a distinctive ontological logic, with dialectics as a core element, not a function of subjective thinking but the animating essence of matter. The focus of the article is Hegel’s stance on the manifestation and reconciliation of freedom, assessing the relationship between individual will and universal practical law. He critiques the limited legal perspective of individual freedom, advocating for a deeper, ethical interpretation of freedom. This view is distanced from common sense and consensus and rooted in speculative understanding developed through scientific and philosophical methods.
Keywords: Hegel; Tragedy; Practical philosophy; Universal practical law; Self-knowledge